A conceptual model of flipped classroom adoption in medical higher education. Issue 4 (12th March 2020) - Abdekhoda, Mohammadhiwa; Maserat, Elham; Ranjbaran, Fatemeh
Abstract : Purpose: Flipped classroom (FC) is a potential approach that encourages active learning and enhances student performance while reducing the failure rate in education. This study was carried out to present the conceptual model of FC adoption by students in higher education. Design/methodology/approach: This was a cross-sectional study in which 110 medical students from Tabriz University of Medical Sciences, Tabriz, Iran, were selected by convenience sampling methods as the sample population. An extended technology acceptance model (TAM) was applied to determine the students' intention concerning the FC adoption. A research-based questionnaire, the validity and reliability of which have been approved, was used as the data collection instrument. The data was analyzed by SPSS v16, IBM. Correlation and regression methods have been used in the empirical study. Finally, the authorized model was presented. Findings: The data show that subjective norms and perceived enjoyment have a direct and significant effect on perceived usefulness of the FC approach ( ß  = 0.32, P -value < 0.05), ( ß = 0.7, P -value < 0.01). Also, we found that perceived usefulness ( ß  = 0.67, P -value < 0.01), perceived ease of use ( ß  = 0.51, P -value < 0.01) and self-efficacy ( ß  = 0.43, P -value < 0.01) have a direct and significant effect on FC adoption. Practical implications: This study extended TAM and presented a validity model to elucidate student's behavior concerning FC acceptance. Also, in this study, five determinant factors that affect successful adoption of FC have been clearly identified. The authors found that the new approach of learning such as FC should be an effective, attractive and enjoyable method. Originality/value: The findings of this study should be considered when successful implementation of FC is in progress.